Predicted increased risk of squamous cell carcinoma induction associated with sunbed exposure habits. (1st July 2015) - Tierney, P.; de Gruijl, F.R.; Ibbotson, S.; Moseley, H.
Summary: Background: Solar ultraviolet radiation (UVR) is recognized as the principal environmental cause of skin cancer. In particular, the risk of induction of squamous cell carcinoma (SCC) has been shown to increase with cumulative exposure to UVR. Models of risk of SCC induction have been developed but these do not include the use of sunbeds. Objectives: To explore the links between sunbed exposure and risk of SCC induction. Methods: To this end, the values of published on‐site UVR levels emitted from sunbeds were used to provide real measured sunbed exposure levels to inform the model. The model incorporated three conditions of exposure: day‐to‐day, holiday and sunbed exposure. The risks associated with different exposure scenarios were implemented in the model. Baseline exposure comprised day‐to‐day and holiday exposure. Relative risk (RR) was defined as the risk of SCC induction from (sunbed + baseline dose)/baseline dose. Results: The RR of SCC induction from estimated median sunbed exposure output [176 standard erythemal dose (SED) per year; 20–35 years of age] in addition to median baseline sun exposure level (166 SED year + 85·5 SED per year holiday) was 1·9 (90% risk increase) up to 55 years of age. A higher sunbed exposure (302 SED per year; 20–35 years of age) produced an RR value of 2·8 (180% increase) at 55 years of age. Conclusions: This is the first time that a risk model for SCC of the skin has been developed that includes estimated sunbed doses derived from measured irradiance data. The model demonstrates that the additional risk associated with sunbed use may be significant, particularly when high‐output, fast‐tan sunbeds are used.